A study on metaphor in English and Vietnamese Business Texts under the topic securities market = Nghiên cứu về ẩn dụ trong các văn bản kinh tế về thị trường chứng khoán - Nguyễn, Thùy Ngân (2021)
To address the research questions with clear and satisfactory answers, the researcher employs observation as the data collection instrument. The process of collecting data includes two main steps. First, the research will skim among various online business articles to understand the general content of the articles on the mentioned sources. Second, the researcher chooses the articles whose contents concern with securities market. Third, for the online articles, the researcher copies them and saves in the format of word documents.